KH Wahab Hasbullah: A Trequartista Political Activist And Initiator Of Nahdlatul Ulama Youth Organisation From The City Of Santri (Jombang) - Hendra Setiawan (Universitas Nahdlatul Ulama Sunan Giri, 2025)
Nahdlatul Ulama (NU) is the largest Islamic organisation in Indonesia, founded in 1926 in Surabaya. Speaking about NU inevitably recalls K.H. Hasyim Asy’ari as the first Rais Am, yet the establishment of NU cannot be separated from the pivotal role of Kiai Wahab Hasbullah. His brilliant ideas were instrumental in NU’s birth, earning acceptance across diverse groups—traditionalists, modernists, and even communists. Wahab Hasbullah was deeply committed to preserving religious traditions while addressing Indonesia’s pressing social issues, including colonial oppression and widespread educational backwardness. His dedication manifested in a spirit of struggle that inspired social change and raised national awareness. In modern Indonesian history, few ulama were as controversial yet influential as Wahab Hasbullah. Across decades of Islamic discourse, his actions often stirred strong emotions. He emerged as a dynamic leader for traditionalist Muslims, guiding them through times of crisis with vision and courage. This study applies a qualitative case study approach supported by literature review. Data sources include key informants, historical documents, books, and both national and international journals relevant to the subject. The analysis uses content analysis techniques to interpret Wahab Hasbullah’s ideas, examining them critically within broader religious and socio-political contexts. The research concludes that Wahab Hasbullah resembled a trequartista in football: a strategist who not only knew when to defend or attack but also mastered off-the-ball movements. Like a trequartista reading the opponent’s tactics, Wahab anticipated challenges and positioned traditionalist Islam as a vital force in Indonesia’s modern history.